MINING STRATEGY AS FORWARD DEFENSE IN FACING THE THREAT OF AMPHIBIAN OPERATION INVASION IN THE WATERS OF THE RIAU ARCHIPELAGO - Hermanto, Lucky Silviana; Faisol, Achmad; Achnaf, Mochamad (AGUSPATI Research Institute, 2025)
This study explores the formulation of a naval mine warfare strategy as a form of forward defense in response to potential amphibious invasion threats in the strategic waters of the Riau Archipelago. Employing Colin S. Gray’s military strategy theory—which emphasizes the link between military power and political objectives—and the policy implementation theory of Mazmanian and Sabatier, the research formulates three main strategies: the phased procurement of new mine warfare vessels, the modernization of modular detection systems, and the enhancement of human resource capacity. These strategies are analyzed using a qualitative approach through SWOT analysis and are designed to involve inter-agency synergy among the Indonesian House of Representatives (Commission I), the Ministry of Defense, the Armed Forces Headquarters (Mabes TNI), and the Navy Headquarters (Mabes TNI AL) to ensure effective implementation on the ground. The findings highlight the importance of policy integration, budgetary support, and technical-operational readiness in establishing a maritime defense posture that is adaptive and responsive to regional threats